(13n+1)=0

Simple and best practice solution for (13n+1)=0 equation. Check how easy it is, and learn it for the future. Our solution is simple, and easy to understand, so don`t hesitate to use it as a solution of your homework.

If it's not what You are looking for type in the equation solver your own equation and let us solve it.

Solution for (13n+1)=0 equation:



(13n+1)=0
We get rid of parentheses
13n+1=0
We move all terms containing n to the left, all other terms to the right
13n=-1
n=-1/13
n=-1/13

See similar equations:

| 6x12(-1)=72 | | 9x-(3x-9)=63 | | |13n+1|=0 | | x=0.6(300+700-0.7x) | | 2x2-–x=0 | | 4(3-5n)-7(5+n)+3=0 | | 3-4x=7x-1 | | 5x-12=3x+13 | | 16-4u=0 | | 5(x-3)=2(2x+6) | | 5(4x/3)=135 | | .06(n-450)=105 | | 70y-6=7 | | 5(11x-)=155 | | f(-3)=-3^2-5(-3)+36 | | 5(11x-)=-28 | | 5x-4=4x-10 | | 3x-11+5x/2=0 | | 6x-3=9x-24 | | 10x=-32-6 | | 7(4x+3)=27x+37 | | 6x-11-7=6(x-3) | | 3−7⋅3+4x=-18 | | 2x+1.9=4.1x+1.27 | | 3.6x-8.4=9.6 | | 2x+2(7-3x)=21 | | F(x)=-2x-5x+7 | | 3x^2+33x-8.1=0 | | 20/13=60/d | | -3x-9=5x+7 | | 12x-48=3x-3 | | 3m+7=97 |

Equations solver categories